2022
DOI: 10.1038/s41598-022-16847-3
|View full text |Cite
|
Sign up to set email alerts
|

Transition from antigenemia to quantitative nucleic acid amplification testing in cytomegalovirus-seropositive kidney transplant recipients receiving preemptive therapy for cytomegalovirus infection

Abstract: Due to the high costs, the strategy to reduce the impact of cytomegalovirus (CMV) after kidney transplant (KT) involves preemptive treatment in low and middle-income countries. Thus, this retrospective cohort study compared the performance of antigenemia transitioned to quantitative nucleic acid amplification testing, RT-PCR, in CMV-seropositive KT recipients receiving preemptive treatment as a strategy to prevent CMV infection. Between 2016 and 2018, 363 patients were enrolled and received preemptive treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…A recent study showed no difference between the antigenemia versus DNAemia tests regarding the incidence and recurrence of CMV infection/disease. 25 The results observed here cannot be extrapolated to other populations, including high-immunological-risk patients, D + /R – CMV serology high-risk KTRs, and pediatric recipients.…”
Section: Discussionmentioning
confidence: 67%
“…A recent study showed no difference between the antigenemia versus DNAemia tests regarding the incidence and recurrence of CMV infection/disease. 25 The results observed here cannot be extrapolated to other populations, including high-immunological-risk patients, D + /R – CMV serology high-risk KTRs, and pediatric recipients.…”
Section: Discussionmentioning
confidence: 67%
“…The antigenemia assay was the only way that was covered by Japanese medical insurance during this study. However, the CMV pp65 antigenemia assay is comparable to CMV QNAT in its ability to provide rapid and sensitive diagnosis of CMV disease and guide treatment options ( Caliendo et al., 2000 ; Pang et al., 2003 ; Razonable and Humar, 2019 ; Nakamura et al., 2022 ). The optimal cut-off value of CMV-Ag in the chronic phase after KTx is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…CMV disease was based on the evidence of CMV replication, regardless of the number of pp65 positive cells or the DNAemia, and associated symptoms. 19 Graft loss was defined as the definitive need to return to dialysis. The biopsy-proven acute rejection (BPAR), including borderline changes, was categorized according to the Banff 2013 classification.…”
Section: Methodsmentioning
confidence: 99%